Heores of Batumi ( Events of March 18-20, in 1921) summary - Gogolishvili, Otar (Politics / პოლიტიკა, 2019)
98 years from the battle for liberation of city. According to the agreement achieved between the head of government of the democratic republic of Georgia Noe Zhordania and chairmen of revolution committee Sergo Kavtaradze, on March 17, 1921, general Giorgi Mazniashvili (1873-1937) gathered soldiers and officers of the Georgian army again and, together with local volunteers, created military subdivision, which liberated Batumi from the foreigner conquerors. Military divisions were created hurriedly and specially. Names and surnames of warriors are not recorded, so the identity of participants and victims of this heroic epopee are still unknown. General Mazniashvili recollects that the number of died heroes was about 84. The military commissar ordered to bury them on the azizya square with a big ceremony, which was implemented on the second day… we buried only 44 killed person, because others were taken in their villages by their parents .